Pro ASP.NET MVC Framework - Sanderson, Steven (Apress, 2012)
We’ve waited a long time for this! The first rough early preview release of ASP.NET MVC was made public in December 2007, and immediately the software development world was filled with eager enthusiasm for it. Could this be the most exciting advancement in Microsoft web technology since ASP.NET itself was born way back in 2002? Would we, at last, have a web development framework that encourages and supports high-quality software engineering?